Changes and their possible causes in δ13C of dark-respired CO2 and its putative bulk and soluble sources during maize ontogeny - Ghashghaie, Jaleh (Journal of experimental botany, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.